O papel mediador de paratextos na leitura literária de estudantes do quarto ano no ensino fundamental - Furtado, Maria Isabel Silveira (My University, 2020)
This dissertation aims to investigate, from the way students interact with examples selected by PNBE 2014, the role of the paratext of these literary works in the choice/reading of a title by children. We propose as a guiding question of this study: How do paratextual elements influence the literary reading of fourth grade students? The theoretical framework that underpins the research privileges Araújo (2008); Genette (2009); Ramos (2010); Colommer and Camps (2008); Kramer (2002); Nikolajeva and Scott (2011); Lyons (2011); Hunt (2014); Zilberman (2003; 2008) and Vygotsky (1998; 2001). As for the methodological procedures, the construction of data occurs through a focus group (GATTI, 2005) and the treatment of the data follows principles of discursive textual analysis (MORAES, 2003; MORAES; GALIAZZI, 2006). This study is qualitative, based on data built on two focus groups and each group had two meetings with two different groups of students from the fourth year of elementary school. The first meeting aimed at the selection of literary books and the second focused on the reading of the chosen works. The empirical data allowed the emergence of the following categories: a) Students' reading preferences; b) Concepts of reading at school and paratexts; c) Library (organization of books - the orientation of literary reading in the library by paratextual elements) and (interaction with paratext in the library); d) Paratext on selection; e) paratext on reading books. The study's conclusions point to the author's title, cover, synopsis, and name as the privileged paratexts in the selection of children's literary works at school. The composition and unfolding of paratexts in selection and reading favor the interaction of students with literary books.
Esta dissertação tem como objetivo investigar, a partir do modo como estudantes interagem com exemplares selecionados pelo PNBE 2014, o papel dos paratextos dessas obras literárias na escolha/na leitura de um título pelas crianças. Propomos como questão orientadora da pesquisa: Que influências os elementos paratextuais de livros literários provocam em estudantes do quarto ano do Ensino Fundamental no que se refere à escolha e à leitura das obras selecionadas? O referencial teórico que sustenta a investigação privilegia Araújo (2008); Genette (2009); Ramos (2010); Colomer e Camps (2008); Kramer (2002), Nikolajeva e Scott (2011); Lyons (2011); Hunt (2014); Zilberman (2003; 2008) e Vygotsky (1998; 2001). Quanto aos procedimentos metodológicos, a construção de dados dá-se por meio de grupo focal (GATTI, 2005) e o tratamento dos dados segue princípios de análise textual discursiva (MORAES, 2003; MORAES; GALIAZZI, 2006). Trata-se de estudo de caráter qualitativo, com base em dados construídos com dois grupos focais com estudantes do quarto ano do Ensino Fundamental. O referencial teórico que embasou a análise dos dados empíricos possibilitou a emergência das seguintes categorias: (a) Os paratextos nos livros preferidos dos estudantes; (b) Concepções de leitura na escola e a presença de paratextos; (c) Biblioteca (organização dos livros – a orientação de leitura literária na biblioteca pelos elementos paratextuais e A retirada de livros da biblioteca apelos a partir de paratextos; (d) Paratextos na seleção e (e) Paratextos na leitura dos livros. As conclusões do estudo apontam para o título, a capa, a sinopse e o nome do autor como os paratextos privilegiados na seleção de obras literárias infantis na escola. Os resultados orientam que os paratextos favorecem a seleção e a interação dos estudantes com os livros literários.
Keywords: Leitura; Paratexto; Literatura infantil; Educação de crianças; Ensino fundamental; Reading; Paratext; Children's literature; Education of children; Elementary School